A rotating tower-like triboelectric nanogenerator for ultrahigh charge density breakthrough. (April 2023) - Zhao, Tiancong; Niu, Bo; Liu, Boying; Li, Zhengyu; Yang, Wenzha; Xie, Guangci; Zhu, Yuanyao; Chen, Dan; Ma, Yong; Hu, Chao
Abstract: In order to extract more electricity from triboelectric nanogenerator (TENG), improving charge density are key issues. Herein, a rotating tower-like triboelectric nanogenerator (RT-TENG) with an innovative circuit which combine discharge tube (DT) with voltage boost circuit (D -VBC) is proposed for ultrahigh charge density breakthrough. This work designs a TENG that stacks multiple tower-like units to achieve charge compensation and systematically analysed the electromechanical coupling performance of blades. Moreover, D -VBC is established to highly improve the power and charge density. Combining the injection and storage of charge with the discharge effect, the surface charge density increases from 457 µC m −2 to 22 mC m −2 (48-fold), and the average power density improves from 41 mW m −2 Hz −1 to 7300 mW m −2 Hz −1, which rapidly charge a 3.3 mF capacitor to 4.2 V within 50 s under the speed of 200 rpm. Furthermore, the power of RT-TENG with 4 tower-like units remains stable after 4 days continuous operation. Thus, this work provides a paradigm for improving the charge density and power of TENGs. Graphical Abstract: The innovative RT-TENG with D -VBC improves the average charge density from 457 µC m −2 to 22 mC m −2 (48-fold). ga1 Highlights: A rotating tower-like triboelectric nanogenerator with an innovative circuit which combine discharge tube with voltage boost circuit is proposed. The electromechanical coupling performance of blades is systematically analysed. This work designs a TENG that stacks multiple tower-like units to achieve charge compensation. Combining the injection and storage of charge with the discharge effect, the surface charge density increases from 457 µC m -2 to 22 mC m -2 (48-fold).